Chlorophyll fluorescence transient analysis and its association with submergence tolerance in rice (Oryza sativa) - PANDA, D; SHARMA, S G (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted in pots during wet season 2004-2005 on the submergence tolerance of 20 rice ( Orzya sativa L.) cultivars by submerging 2-week-old seedlings for 2,4,6,8 and 10 days. Measurements of chlorophyll fluorescence were done on the cut off dark adapted fully expanded second and third leaves from the top after 1 hr of desubmergence. Correlation coefficients were calculated between different chlorophyll fluorescence parameters and survival percentage. With increasing duration of submergence different fluorescence parameters especially variable fluorescence, potential quantum yield of primary photochemistry, area above the minimal and maximal fluorescence curve, electron transport and number of reaction centres per excited cross section decreased with higher magnitude in susceptible cultivars compared to tolerant ones. A highly significant positive association between survival percentage and various chlorophyll fluorescence parameters was observed which suggested that fluorescence measurements provide the information about the survival chance of rice plants under submerged conditions.